An economic analysis of wheat variety selection in Kansas, 1990-2016 - He, Jiajing (Kansas State University, 2017)
From 1990 to 2016, the Kansas wheat varieties with milling and baking quality rated as “Less Desirable” accounted for 22% of all wheat acres planted, compared with 36% during the period 1974 to 1993. Thus, wheat producers have selected wheat varieties with lower end-use quality over time. Regression analysis was used to identify and quantify the determinants of planted wheat varieties in Kansas over the time period 1990 to 2016. The results show that Kansas wheat producers make variety decisions primarily based on relative yield and previously planted varieties. Wheat producers also consider the end-use qualities on test weight and milling and baking quality. There were more varieties planted in 1990-2016 than during the 1974-1993 period, and producers have planted with a greater emphasis on yield than other production characteristics.
Keywords: Wheat; Wheat variety selection